Pengaruh Komunikasi dari Mulut ke Mulut terhadap Citra Merek dan Reputasi Perusahaan serta dampaknya pada Nilai Pelanggan - Julina Julina (Sosial Budaya, 2018)
This study aims to determine the effect of word of mouth on the brand image and company reputation and its impact on customer value. Data were collected using a questionnaire containing statements about the variables studied. After tested the validity and reliability, the data then analyzed using simple and multiple regression. The results found no effect of word of mouth on the brand image and corporate reputation, while there was a positive and significant influence between the brand image and the company's reputation on customer value.